When actions speak louder than words: examining collective political protests in Central Asia. Issue 4 (6th June 2016) - Achilov, Dilshod
Abstract : What explains the dynamics of contentious collective political action in post-Soviet Central Asia? How do post-Soviet Central Asian citizens negotiate the tensions between partaking in and abstaining from elite-challenging collective protests? By analysing cross-national attitudes in two Central Asian states, this article (1) systematically analyses the variation in collective protests by testing rival macro-, meso-, and micro-level theories; (2) reintroduces a conceptual and empirical distinction between low-risk and high-risk collective protests; and (3) examines the conditions under which individuals participate in two distinct types of elite-challenging collective actions. Three conclusions are reached. First, the evidence suggests that nuanced consideration of multi-level theoretical perspectives is necessary to explain contingencies of elite-challenging actions. Second, economic grievances and resource mobilization emerge as leading factors driving both low-risk and high-risk protests. Third, Islamic religiosity and social networking robustly predict participation in high-risk collective action.